TINJAUAN ATAS SOSIALISASI PERPAJAKAN DAN PERAN ACCOUNT REPRESENTATIVE DALAM KEPATUHAN WAJIB PAJAK (STUDI KASUS KPP PRATAMA BATU MALANG) - Rosiane Florentina Ningrum (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This Research discusses the implementation of the socialization of taxation and Account Representative role in helping taxpayer meet the obligations of taxation in KPP Pratama Batu Malang. The purpose of this study was to describe the ways and constraints of socialization and the role of Account Representative encountered in KPP Pratama Batu Malang in improving taxpayer compliance. This study is a qualitative research with descriptive design. Methods of data collection in this study using a structured interview with four Account Representative and Head of Supervision and Consultation section on KPP Pratama Batu Malang was the focus on the discussion in this study. Sources of data that researchers use were analyzed descriptively. These results indicate the low awareness of their obligations as taxpayers. It is expected the active role of Account Representative and the routine conduct of socialization of taxation that still must be improved not only in the material submitted, but in terms of means and methods used. Keywords: Socialization of taxation, the role of Account Representative, tax compliance